Political leadership as a foundation for consolidating flat hierarchies in agile governance models for sustainable development under conditions of digital transformation - Gibadullin , Oleksii (Pressing Problems of Public Administration, 2025)
The article focuses attention on the possibility of restoring balance between sustainable development governance systems and socio-economic transformation processes through changing approaches to utilising political leadership practices, which continue to persist in the intangible emotional potential of the social component. The scholarly trajectory of reconceptualising political leadership as a consolidating element of contemporary transformation processes within a dynamic horizon places particular emphasis on the interconnection between leadership and governance processes, and the interdependence of political leadership and information flow sustainability. This may facilitate alignment and balancing of the evolutionary trajectory of the sustainable development system with approaches to constructing governance processes. Furthermore, utilising emotional capital, creative inquiry, and technological capacity can create an internal climate conducive to fostering a culture of organic change. The aim of this article is to provide scholarly substantiation for the possibility of optimally constructing a governance system based on utilising the emotional influence of renewed political leadership as an element of component integration, ensuring structural flexibility and information channel sustainability.The author emphasises that the growing significance of information as a formative element transforms the internal structure of integration, balancing, and ordering processes, wherein traditional governance hierarchies, in terms of flow ordering levels and information processing speed, are unable to prevent crises and challenges, yet remain the evolutionary foundation of institutional changes in public-private relations. The author asserts that alignment and balancing of the sustainable development governance system with socio-economic transformation processes can presently be realised on the basis of a continuum of more adaptive governance models and reconceptualization of political leadership’s significance as a consolidating element. The author notes that unlocking the potential of shared leadership in renewed governance models, on the one hand, aligns the value-objective chain, whilst on the other, extends its dissemination throughout the system structure, harmonising internal processes. Combining disparate parts into a unified system around shared values creates, on the one hand, a foundation for forming flat hierarchies, whilst on the other, accelerates information exchange and reduces discrete attenuation of managerial influence. Consolidating process actors around a unified political strategy enables continuous reassessment of effectiveness, balancing external commitments with internal context, and comprehensive process improvement.The article reveals the conceptual and methodological foundations for renewing approaches to constructing sustainable development governance processes through aligning contemporary transformation trajectories with approaches to building management systems. The reconceptualization of leadership’s significance is examined within the dimension of organic consolidation and balanced ordering of internal sustainable development processes during the implementation of contemporary agile governance models.